Student responses to the electronic module of the circulatory system - Syafira Amelia; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Mangifera Edu, 2022)
The use of electronic teaching materials could increase students’ interest in learning. An electronic module was one of the teaching materials. This study aimed to see the feasibility of the electronic module material for the circulatory system. We used the research and development method. This study’s method had steps that included potential and problems, data collection, product design, design validation, design revision, and product testing. Five validators validated product design. The data analysis used the CVR and CVI values for each criterion in the validation aspect which are course, graphic, contents, and language with a minimum value of 0.99. The study found two important findings. First, from the validator, the CVR values in all elements had a value of 1, and the CVI results each had a value of 1. Hence, the electronic module of the circulatory system material is declared valid and feasible to use. Second, the product trial obtained an overall average score of 88.4% and was very positive. It means that the electronic module could be an alternative teaching material used in the learning process at school or self-study for the student at home.